Pengaruh Pembiayaan Murabahah Dan Musyarakah Terhadap Profitabilitas Pada PT. Bank Syariah Mandiri - Riyan Pradesyah; Nur Aulia (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2021)
The purpose of this study was to analyze the effect of Murabahah Financing, Musyarakah Financing on Profitability at PT. Bank Syariah Mandiri. The data used is secondary data taken from the Monthly Financial Reports of Bank Syariah Mandiri for the period 2016-2020 / August. This type of research is quantitative research. The population in this study were all monthly financial reports of PT. Bank Syariah Mandiri 2016-2020 / August. The sample of this research is data on Murabahah Financing, Musharaka Financing and Return On Asset (ROA) contained in the financial statements of PT. Bank Syariah Mandiri published by the Financial Services Authority (OJK) and uses a purposive sampling method. The method of analysis uses multiple linear regression analysis, taking into account the Classical Assumption Test and Hypothesis Test. The results of the analysis of this study concluded that 1) Murabahah financing had no effect on ROA, as evidenced by the result of tcount -0.569 ttable 1.67412 with sig 0.572 0.05. 2) Musharaka financing has an effect on ROA, as evidenced by the results of tcount 5,179 ttable 1,67412 with sig. 0.000 0.05. 3) Murabahah Financing and Musharaka Financing together have an influence on ROA as evidenced by the existence of Fcount 17.076 Ftable 3.17 and the sig value 0.000 0.05.